Modular-designed engineered bacteria for precision tumor immunotherapy via spatiotemporal manipulation by magnetic field - Ma, Xiaotu; Liang, Xiaolong; Li, Yao; Feng, Qingqing; Cheng, Keman; Ma, Nana; Zhu, Fei; Guo, Xinjing; Yue, Yale; Liu, Guangna; Zhang, Tianjiao; Liang, Jie; et al. (Nature communications, 2023)
Micro-nano biorobots based on bacteria have demonstrated great potential for tumor diagnosis and treatment. The bacterial gene expression and drug release should be spatiotemporally controlled to avoid drug release in healthy tissues and undesired toxicity. Herein, we describe an alternating magnetic field-manipulated tumor-homing bacteria developed by genetically modifying engineered Escherichia coli with Fe 3 O 4 @lipid nanocomposites. After accumulating in orthotopic colon tumors in female mice, the paramagnetic Fe 3 O 4 nanoparticles enable the engineered bacteria to receive and convert magnetic signals into heat, thereby initiating expression of lysis proteins under the control of a heat-sensitive promoter. The engineered bacteria then lyse, releasing its anti-CD47 nanobody cargo, that is pre-expressed and within the bacteria. The robust immunogenicity of bacterial lysate cooperates with anti-CD47 nanobody to activate both innate and adaptive immune responses, generating robust antitumor effects against not only orthotopic colon tumors but also distal tumors in female mice. The magnetically engineered bacteria also enable the constant magnetic field-controlled motion for enhanced tumor targeting and increased therapeutic efficacy. Thus, the gene expression and drug release behavior of tumor-homing bacteria can be spatiotemporally manipulated in vivo by a magnetic field, achieving tumor-specific CD47 blockage and precision tumor immunotherapy. Several strategies have been employed to enhance the tumor-targeting and anti-cancer properties of engineered bacteria. Here the authors describe the design of alternating magnetic field-manipulated bacteria engineered to release an anti-CD47 nanobody, promoting anti-tumor immune response in preclinical cancer models.